Phenolics Profile and Antioxidant Activity Analysis of Kiwi Berry (Actinidia arguta) Flesh and Peel Extracts From Four Regions in China - Zhang, Jiyue; Gao, Ningxuan; Shu, Chi; Cheng, Shunchang; Sun, Xiyun; Liu, Changjiang; Xin, Guang; Li, Bin; Tian, Jinlong (Frontiers in Plant Science, 2021)
The kiwi berry (Actinidia arguta) has been widely studied because of its rich phenolic, flavonoid, and vitamin C contents. Numerous reports have demonstrated that fruit peels contain higher phenolic content and antioxidant activity than that of flesh. In this study, the phytochemical content and antioxidant activities of peel and flesh extracts of six kiwi berries were analyzed from four regions (namely, Dandong, Benxi, Taian, and Tonghua) in China. The antioxidant activity was determined using the peroxyl radical scavenging capacity (PSC) and cellular antioxidant activity (CAA) assays. The phenolic, flavonoid, and vitamin C contents of kiwi berry peel were 10.77, 13.09, and 10.38 times richer than that of kiwi berry flesh, respectively. In addition, the PSC and CAA values of kiwi berry peel were higher than those of kiwi berry flesh. The analysis of the separation and contents of phenolics were performed by the high-performance liquid chromatography (HPLC)-diode-array detectormass spectrometry/mass (DAD-MS/MS) system, and the results illustrated that protocatechuic acid, caffeic acid, chlorogenic acid, and quinic acid were the major phenolic compounds. In conclusion, this study indicated that kiwi berry peel contains a rich source of antioxidants. These data are of great significance for the full development and utilization of kiwi berries in these four regions of China to produce nutraceutical and functional foods.